The Role of Intrapreneurship for Sustainable Innovation through Process Innovation in Small and Medium-sized Enterprises: A Conceptual Framework - Widya-Hastuti, A.; Talib, Noraini Bt Abu; Wong, Kuan Yew; Mardani, Abbas (International Journal of Economics and Financial Issues, 2016)
A focus on innovation alone is not sufficient for sustainability in the current hostile business environment. Environment awareness and social impact as well as economic place demands on firms to contribute to sustainable development. As such, there is increased interest in sustainable innovation. On the other sides, intrapreneurship spirit of internal initiative of a firm as firm-specific capabilities is proposed to facilitate this. In the manufacturing firms, process is considered as critical and source to be innovative. Hence, process innovation is utilized to translate intrapreneurship capability for sustainable innovation. To face new circumstances in the business environment for the sustainability of SMEs, the role of intrapreneurship in transforming process innovation under existing technology for sustainable innovation achievement is another interesting view to be explored. This paper discusses the role of intrapreneurship in attaining sustainable innovation through process innovation in SMEs and develop it into an integrated framework. The framework shows that the elements of proactiveness, risk taking and autonomy in intrapreneurship provides a leverage for sustainable economic, environmental and social innovation. The study further suggests empirical investigation in the firms for future research. Keywords: Sustainable innovation; Intrapreneurship; Process innovation JEL Classification: Q56